Assessment of OATP transporter‐mediated drug–drug interaction using physiologically‐based pharmacokinetic (PBPK) modeling – a case example. (20th November 2018) - Chen, Yuan; Zhu, Rui; Ma, Fang; Mao, Jialin; Chen, Eugene C.; Choo, Edna F.; Sahasranaman, Srikumar; Liu, Lichuan
Abstract: GDC‐0810 was under development as an oral anti‐cancer drug for the treatment of estrogen receptor‐positive breast cancer as a single agent or in combination. In vitro data indicated that GDC‐0810 is a potent inhibitor of OATP1B1/1B3. To assess clinical risk, a PBPK model was developed to predict the transporter drug–drug interaction (tDDI) between GDC‐0810 and pravastatin in human. The PBPK model was constructed in Simcyp® by integrating in vitro and in vivo data for GDC‐0810. The prediction of human pharmacokinetics (PK) was verified using GDC‐0810 phase I clinical PK data. The Simcyp transporter DDI model was verified using known OATP1B1/1B3 inhibitors (rifampicin, cyclosporine and gemfibrozil) and substrate (pravastatin), prior to using the model to predict GDC‐0810 tDDI. The effect of GDC‐0810 on pravastatin PK was then predicted based on the proposed clinical scenarios. Sensitivity analysis was conducted on the parameters with uncertainty. The developed PBPK model described the PK profile of GDC‐0810 reasonably well. In the tDDI verification, the model reasonably predicted pravastatin tDDI caused by rifampicin and gemfibrozil OATP1B1/3 inhibition but under‐predicted tDDI caused by cyclosporine. The effect of GDC‐0810 on pravastatin PK was predicted to be low to moderate (pravastatin Cmax ratios 1.01–2.05 and AUC ratio 1.04–2.23). The observed tDDI (Cmax ratio 1.20 and AUC ratio 1.41) was within the range of the predicted values. This work demonstrates an approach using a PBPK model to prospectively assess tDDI caused by a new chemical entity as an OATP1B1/3 uptake transporter inhibitor to assess clinical risk and to support development strategy.